Influência do banho de aspersão ante-mortem na eficiência da sangria e em parâmetros bioquímicos da carne bovina - Roca, R. D.; Serrano, A. D. (Empresa Brasileira de Pesquisa Agropecuária (EMBRAPA), 1995)
To determine the effects of the pre-slaughter showering on some meat quality parameters, the biochemical changes in the Longus colli muscle and the bleeding efficiency were studied. Thirty-six Nelore steers were slaughtered in a commercial slaughterhouse. Eighteen animals were submitted to pre-slaughter showering; a control group of eighteen animals were slaughtered without showering. Samples were collected for evaluations in the muscle depth, in the anterior portion of longus colli muscle,just before chilling. Bleeding efficiency was evaluated through the ratio of muscle haemoglobin/blood haemoglobin using blood samples taken five seconds after bleeding, and muscle sample taken before chilling. Longus colli muscle samples were also used to determine glycogen, glucose, pH and acidity, 5, 24 and 48 hours after slaughtering. Multivariate methods were used to evaluate biochemical data and the bleeding efficiency data analysis followed the randomized block design. Haemoglobin retained in the muscle and bleeding efficiency were not affected (P > .05) by pre-slaughter showering. The pre-slaughter showering did not affect (P > .05) the glycolysis. There was a significant effect of time in glycogen, glucose, pH and acidity, in the first 24 hours.

0 trabalho teve como objetivo avaliar a influência do banho de aspersão antes do abate em alguns parâmetros bioquímicos da qualidade da carne bovina e na eficiência da sangria. Foram utilizados 36 bovinos da raça Nelore, abatidos em matadouro-frigorífico, sendo 18 animais submetidos ao banho de aspersão, e 18 animais não-submetidos ao banho. Foram colhidas amostras na porção torácica do músculo Longus colli, no início do resfriamento da carcaça. Nas amostras de músculo, foram feitas as determinações de glicogênio, glicose, pH e acidez, após 5, 24 e 48 horas do abate. A eficiência da sangria foi avaliada pela diferença entre as determinações do teor de hemoglobina em amostras de sangue, colhido cinco segundos após o corte dos vasos sangüíneos, e na mesma amostra do músculo Longus colli empregada nas outras determinações. Foi empregada análise multivariada nos resultados obtidos. 0 teor de hemoglobina retido no músculo e a eficiência da sangria não foram afetados pelo banho de aspersão. Verificou-se que o banho de aspersão antes do abate não afetou (P > 0,05) o perfil da glicólise. Houve efeito significativo do tempo após o abate nas determinações de glicogênio, glicose, pH e acidez, nas primeiras 24 horas; não ocorreu o mesmo efeito no período entre 24 e 48 horas após o abate.
The effects of the pre-slaughter showering on bleeding efficiency and biochemical changes of beef
Keywords: slaughter; carcass; glycolysis; haemoglobin; slaughterhouse